Marketing communications of the Organizing committee «Kiev City marathon – 2014» - Olena Yarmolyuk; Anna Zolotaryova (Слобожанський науково-спортивний вісник, 2015)
Purpose: to share the experience of the marketing communications’ application in the physical culture and sports sphere and to improve the commercial activities of sports organizations during the planning and holding the mass sporting events. Material and Methods: the basic forms and methods of the sponsorship activities of the Organizing Committee of the competition «Kiev Marathon – 2014» were analyzed with system analysis, SWOT-analysis and sociological questioning (12 specialists from the Organizing Committee of «Kiev City Marathon – 2014» and 95 visitors of the «Kiev City Marathon – 2014» were questioned). Results: the main channels of marketing communications. Such as, external advertising media, publicity in the subway (light boxes and video- broadcasting), indoor video (in restaurants and supermarkets), publicity at the radio stations, in newspapers and sports editions, printed promo-products, campaign in «Sport Life» fitness clubs, were used during advertising campaign. Conclusions: the results of research given in the article will enable professionals to most effectively use tools of marketing communications in the physical culture and sports sphere, as well as to introduce modern mechanisms of interaction between mass-media and sporting organizations.